ANALISIS USAHATANI KELAPA SAWIT POLA SWADAYA PADA LAHAN BASAH DI KABUPATEN INDRAGIRI HILIR - Riyadi Mustofa (LPPM Universitas Muhammadiyah Sumatera Barat, 2017)
Palm oil can be grown in various typologies land either on dry land or in wetlands. Wetlandsare as show the marginal land, that palm oil plantation by pattern sel help indented with lowproductivity. The study was conducted to determine the productivity of the land and the level ofprofit achieved by the farmers self-help in the wetlands and compute efficiency whether it isfeasible and profitable farming. The analysis is the analysis of farming for calculating theamount of input and output of a series of activities ranging from land clearing to harvesting.The results obtained show that the productivity of oil palm farming in the wetlands nonIndragiri Hilir of 8766 kg / ha / year with an average price for one year is Rp. 774 / kg. theproductivity of the land and the price farmers suffered an average loss of Rp. 52 522 / ha / yr.Acceptance of farmers over the years is the cost of depreciation on plant and non-plant whichis considered as income.Keywords:Income, Product, Wetlands